Analisis Kualitas Pelayanan Identitas Kependudukan Digital (IKD) di Dinas Kependudukan dan Pencatatan Sipil Kota Mojokerto - Ilham Ramdhani; Trenda Aktiva Oktariyanda; Meirinawati M; Eva Hany Fanida (Socius: Jurnal Penelitian Ilmu-Ilmu Sosial, 2026)
Population administration services are an essential part of public services in fulfilling citizens’ basic rights. As an effort to modernize digital-based services, the Directorate General of Population and Civil Registration introduced the Digital Population Identity (IKD) service. However, the implementation of IKD at the Department of Population and Civil Registration of Mojokerto City still faces various technical and service-related challenges. This study aims to describe the quality of IKD services using seven digital service quality indicators proposed by (Aljukhadar et al., 2022). This research employs a descriptive qualitative approach, with data collected through interviews, observations, and documentation, and analyzed using the Miles and Huberman model. The findings indicate that the quality of IKD services has not yet been fully optimized, particularly in terms of interactivity, information and assistance quality, ease of use, system stability, public understanding of data privacy and security, and application interface design. Therefore, strengthening the application system, improving digital information and assistance, and developing a more user-friendly application design are recommended to enhance the quality of IKD services in the future.